Prostaglandin Synthesis, Metabolism, and Signaling Potential in the Rhesus Macaque Corpus Luteum throughout the Luteal Phase of the Menstrual Cycle - Bogan, Randy L. (The Endocrine Society, 2008)
Prostaglandins in the corpus luteum (CL) reportedly serve as luteotropic and luteolytic agents. Based mainly on studies conducted in domesticated animals and rodents, prostaglandin E2 (PGE2) is generally considered a luteotropic factor, whereas uterine-derived prostaglandin F2α (PGF2α) initiates luteolysis. However, the role of prostaglandins in regulating primate luteal structure-function is poorly understood. Therefore, a comprehensive analysis of individual mRNA or proteins that are involved in PGE2 and PGF2α biosynthesis, metabolism, and signaling was performed using CL obtained at distinct stages of the luteal life span during the menstrual cycle in rhesus monkeys. Peak levels of proteins involved in PGE2 synthesis (prostaglandin-endoperoxide synthase 2, microsomal PGE2 synthase-1) and signaling (PGE2 receptor 3) occurred during periods corresponding to development and maintenance of the primate CL. Immunohistochemistry studies indicated that large luteal cells express PGE2 synthesizing and signaling proteins. Expression of PGE2 synthesizing and signaling proteins significantly decreased preceding the period of functional regression of the CL, which also coincided with increasing levels of PGF2α receptor protein expression within the large luteal cells. Moreover, significant levels of mRNA expression for several aldoketo reductase family members that synthesize PGF2α from other prostaglandins were observed throughout the rhesus macaque luteal phase, thus supporting the possibility of intraluteal PGF2α production. Collectively, our results indicate that there may be intraluteal synthesis and signaling of PGE2 during development and maintenance of the primate CL, followed by a shift to intraluteal PGF2α synthesis and signaling as the CL nears the time of luteolysis.